Financial development as a catalyst for tax revenue generation in Ghana: exploring the channels - Kofi Kamasa; Ellen Korsah; Isaac Bonuedi; Priscilla Forson (Scientific African)
This paper investigates the effect of financial sector development in driving tax revenue generation in Ghana, as well as the channels through which this may occur. The paper utilizes an annual time-series dataset over the period 1980 – 2021. The auto-regressive distributed lag (ARDL) cointegration technique is employed as the main estimation strategy, with the fully modified least squares (FMOLS) and canonical cointegrating regression (CCR) cointegration techniques serving as robustness checks. The findings reveal that financial development significantly enhances tax revenue generation in the long run, with indirect, corporate, and income taxes showing a higher sensitivity to financial sector development over the long run. Furthermore, the study identifies a reduction in the shadow economy, plausibly through the formalization of informal sector activities, as a critical pathway through which financial development contributes to improved tax revenue generation. Finally, it is found that effective control of corruption, better human capital development (education), and economic growth (higher GDP) constitute significant drivers of Ghana’s tax revenue in the long run. The study recommends the enforcement of stricter regulations to ensure tax compliance within financial institutions, fostering closer collaboration between tax authorities and financial institutions to facilitate the exchange of relevant information, and improving tax administration processes to ease taxpayer compliance.